Condemned homicide offenders and externalizing psychopathology - Peters, David J. (Routledge handbook of homicide studies, 2024)
Previous research shows that homicide offenders exhibit above-average externalizing psychopathy that is strongly correlated with criminal career. However, it is unknown whether these findings apply to offenders who have committed especially severe or aggravated homicides that have resulted in a capital conviction. To address this gap, we identify distinct psychopathy profiles using latent class analysis (LCA); and then describe demographic and criminal history differences across profiles. Using archival data and appellate records, a unique large-scale database of 636 condemned capital murderers in California was constructed to measure psychopathy (PCL-R), antisocial personality disorder (ASPD), and sexual sadism. Results of the LCA find that 16% of capital homicide offenders exhibit few signs of psychopathy, ASPD, or sexual sadism, with scores very close to the non-criminal general population. By contrast, 26% fell into the upper-range psychopathy class, with externalizing psychopathy far above those of general homicide offenders. At the extreme end, the 31% of condemned murderers in the clinical psychopathy class stood out. ASPD and sexual sadism disorder rates were ten times higher. Rates of attempted and prior murders were ten to 20 times higher, and murder of inmates in prison was 130 times higher. Clinical psychopaths were three times more likely to kill victims using manual strangulation, and 30 times more likely to engage in necrophilic activity with victims.